Current landscape of personalized clinical treatments for triple-negative breast cancer - Zhang, Jun; Xia, Yu; Zhou, Xiaomei; Yu, Honghao; Tan, Yufang; Du, Yaying; Zhang, Qi; Wu, Yiping (Frontiers in Pharmacology, 2022)
Triple-negative breast cancer (TNBC) is a highly malignant subtype of breast cancer (BC) with aggressive biological behaviors. TNBC is usually associated with relatively poor clinical outcomes, earlier recurrence, and high propensity for visceral metastases than other BC types. TNBC has been increasingly recognized to constitute a very molecular heterogeneous subtype, which may offer additional therapeutic opportunities due to newly discovered cancer-causing drivers and targets. At present, there are multiple novel targeted therapeutic drugs in preclinical researches, clinical trial designs, and clinical practices, such as platinum drugs, PARP-1 inhibitors, immunocheckpoint inhibitors, androgen receptor inhibitors as well as PI3K/AKT/mTOR targeted inhibitors. These personalized, single, or combinational therapies based on molecular heterogeneity are currently showing positive results. The scope of this review is to highlight the latest knowledge about these potential TNBC therapeutic drugs, which will provide comprehensive insights into the personalized therapeutic strategies and options for combating TNBC.